2009
DOI: 10.1111/j.1365-2516.2008.01915.x
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis in 10 patients with severe haemophilia A and inhibitor: different approaches for different clinical situations

Abstract: The effect of bypassing agents is not as predictable as replacement therapy with the deficient factor in inhibitor patients. Consequently, these patients have more levels of arthropathy than patients without inhibitors. Prophylaxis for inhibitor patients has gained attention over the last decade and some papers have reported that bypassing agents could work in the prevention of arthropathy. However, there is a lack data to support any specific agent or regimen or even to recommend their use in different clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 32 publications
1
64
1
1
Order By: Relevance
“…Nonetheless, most patients in the study had an excellent response to prophylaxis, confirming anecdotal reports of a reduction in bleeding associated with long-term AICC prophylaxis. [13][14][15]22 This demonstrated efficacy raises the possibility that primary AICC prophylaxis in children with inhibitors, when started at a young age and before the development of repeated joint bleeding, could provide benefits similar to those in children with severe hemophilia A who are receiving * This allergic reaction was noted while the drug was being infused, and the infusion was discontinued prematurely. † This event was deemed to be related to study participation.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, most patients in the study had an excellent response to prophylaxis, confirming anecdotal reports of a reduction in bleeding associated with long-term AICC prophylaxis. [13][14][15]22 This demonstrated efficacy raises the possibility that primary AICC prophylaxis in children with inhibitors, when started at a young age and before the development of repeated joint bleeding, could provide benefits similar to those in children with severe hemophilia A who are receiving * This allergic reaction was noted while the drug was being infused, and the infusion was discontinued prematurely. † This event was deemed to be related to study participation.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Recent publications have highlighted the potential role of rFVIIa in prophylaxis of hemophilic patients with inhibitors. 14,16,17 Although the mechanisms of action of rFVIIa in the correction of active bleeding have been widely studied, those involved in the apparent long-lasting effects of rFVIIa for prophylactic treatment remain to be clarified. It has been speculated that a portion of the rFVIIa infused into patients could diffuse to the extravascular space and, once there, become available at the site of injury.…”
mentioning
confidence: 99%
“…However, consensus is still required with respect to key aspects of prophylaxis including the benefit of this approach in relation to ITI. To address this need, a group of Spanish expert haematologists with pioneering experience specifically in the prophylactic treatment of haemophilia patients with high-titre inhibitors to FVIII (26)(27)(28)(29) undertook a critical review of the current scientific evidence and reached a consensus view on key management aspects. It should be noted that at the time of writing these recommendations rFVIIa is not licensed for prophylaxis in Spain.…”
Section: Discussionmentioning
confidence: 99%
“…In one case report, Jiménez-Yuste et al (27) reported the administration of primary prophylaxis in one patient aged 24 months who had suffered three episodes of bleedings related to trauma. In a case series of 10 patients, the same authors reported the administration of primary prophylaxis in two patients aged 25 and 34 months who were receiving on-demand treatment with FVIII due to multiple bleedings (other than joint bleedings) (29). Also, 'continuation of prophylaxis' from FVIII to rFVIIa was indicated in a child aged 18 months who had also suffered one joint bleed after the development of inhibitors (29).…”
Section: Pre-iti Periodmentioning
confidence: 99%